KARAKTERISASI SENYAWA FENOLIK DARI BIJI BUAH RAMBUTAN (Nephelium lappaceum L.) - Eka Pebri Malinda; Rudiyansyah Rudiyansyah; Ajuk Sapar (Indonesian Journal of Pure and Applied Chemistry, 2019)
Rambutan seeds are one of the waste produced from rambutan that is potential to be used in the food and pharmaceutical fields because it is rich in nutrients and secondary metabolites. This research was carried out to characterize phenolic compounds from the ethyl acetate fraction by using chromatographic methods, phytochemical tests, and 1H-NMR analysis. The isolate was obtained as white powder with 6.2 mg and gave positive sign for phenolic by phytochemical test. 1H-NMR spectrum data (CD3OD, 500 MHz) showed the chemical shift characteristic of coumarin compounds at δH (ppm): 7.82 (1H, d, J= 8.3 Hz), 7.39 (1H, d, J= 7.55 Hz), 6.73 (1H, d, J= 8.05 Hz), and 5.61 (1H, d, J= 7.55 Hz), an anomeric proton at δH 4.8-5 ppm, the characteristics of the methyl group of L-rhamnose sugar at δH 1.29 ppm and other sugar protons at δH 3-4 ppm. Based on the 1H-NMR analysis and comparison with literature, a phenolic compound obtained from rambutan (Nephelium lappaceum L.) seeds is                            7-O-β-L-rhamnose-8-hydroxycoumarin or 8-O-β-L-rhamnose-7-hydroxycoumarin.